Anti-money Laundering Regulations and Compliance among Financial Institutions in Ghana: The Moderating Role of Ethical Leadership and Capacity of Organization - Asamoah, Emmanuel Selase (International Journal of Economics and Financial Issues, 2026)
Globalization has fostered increased integration across information, finance, and technology sectors worldwide, fuelling economic expansion. However, this interconnectedness has also introduced heightened risks, with money laundering emerging as a critical global issue. While Ghana has set up preventative systems, the actual vigour of enforcement and clarity on the prosecution of offenders remain questionable. The aim of this research is to assess Anti-Money Laundering (AML) regulations and compliance among financial institutions. The study sampled 874 participants from 34 financial institutions in Ghana. Structural Equation Modelling was employed to examine the link between legal enforcement mechanisms and AML compliance, considering organizational capacity and ethical leadership as mediators. It was found that if the AML regulations will succeed in making an impact in the financial sector, then financial institutions must prioritize building organizational capacity, as this variable mediates the relationship between AML regulations and compliance. Interestingly, the study found that ethical leadership did not moderate the relationships between AML regulations, institutional capacity, and compliance. The findings enrich ongoing dialogues surrounding AML compliance and its symbiotic relationship with AML adoption. The findings are instrumental in carving robust AML policy blueprints both for Ghana and its neighbouring regions, offering pivotal guidance to regulatory entities and policymakers in amplifying their AML endeavours.